Hantaviral mechanisms driving HLA class I antigen presentation require both RIG-I and TRIF - Lalwani, Pritesh Jaychand; Raftery, Martin J.; Kobak, Lidija; Rang, Andreas; Giese, Thomas; Matthaei, Markus; van den Elsen, Peter J.; Wolff, Thorsten; Krüger, Detlev H.; Schönrich, Günther (European journal of immunology, 2013)
Hantaviruses are emerging human pathogens. They induce an unusually strong antiviral response of human HLA class I (HLA-I) restricted CD8+ T cells that may contribute to tissue damage and hantavirus-associated disease. In this study, we analyzed possible hantaviral mechanisms that enhance the HLA-I antigen presentation machinery. Upon hantavirus infection of various human and primate cell lines, we observed transactivation of promoters controlling classical HLA molecules. Hantavirus-induced HLA-I upregulation required proteasomal activity and was associated with increased TAP expression. Intriguingly, human DCs acquired the capacity to cross-present antigen upon hantavirus infection. Furthermore, knockdown of TIR domain containing adaptor inducing IFN-β or retinoic acid inducible gene I abolished hantavirus-driven HLA-I induction. In contrast, MyD88-dependent viral sensors were not involved in HLA-I induction. Our results show that hantaviruses strongly boost the HLA-I antigen presentation machinery by mechanisms that are dependent on both retinoic acid inducible gene I and TIR domain containing adaptor inducing IFN-β.
Gesehen am 22.09.2021